Os Tupi Guarani de Barão de Antonina-SP: migração, território e identidade - Almeida, Lígia Rodrigues de (Universidade Federal de São Carlos, 2011)
This thesis discusses how the Tupi Guarani who live in the district of Barão de Antonima, in the southwest of São Paulo state, conceive their territory in the context of demarcation of indigenous lands. Considering that the area they inhabit is currently undergoing under a process of demarcation. It also reflects how this indians rethink this context of territorial shifts, referring themselves as definers of their territories. And discussing the way how the myth treats about seeking for Lands free from evils. It (re) means locating the place where this land can be found. Not in the east, how the classical biography presents, but in all those places that the ancestors lived in, assuming different ways and contexts. The investigations carried out in the field articulated the bibliography review wish made me believe that if the demarcation of the lands didn't make sense to the Tupi Guarani groups, nowadays it became necessary. It's a way to guarantee inhabitable spaces where those groups would be able to reproduce their life style. This way it's not about the limitation of the movement or the fixation on a delimitated territory, but a way to guarantee that those groups continue to dislocate around a vast territory, circulating around villages and around demarcated indigenous lands.
Keywords: Antropologia social; Mito; Etnia; Território; Tupi guarani; São Paulo; Territory; Tupi Guarani; São Paulo; CIENCIAS HUMANAS::ANTROPOLOGIA